Affect and Health Behavior Co-Occurrence: The Emerging Roles of Transdiagnostic Factors and Sociocultural Factors. (January 2016) - Zvolensky, Michael J.; Leventhal, Adam M.
The majority of scientific work addressing relations among affective states and health correlates has focused primarily on their co-occurrence and a limited range of health conditions. We have developed a Special Issue to highlight recent advances in this emerging field of work that addresses the nature and interplay between affective states and disorders, in terms of their impact and consequences from health status and behavior. This Special Issue is organized into three parts classified as (a) co-occurrence and interplay between (b) transdiagnostic factors and (c) sociocultural factors. It is hoped that this issue will (a) alert readers to the significance of this work at different levels of analysis, (b) illustrate the many domains currently being explored via innovative approaches, and (c) identify fecund areas for future systematic study.